The Magic rings - Harrison, Paula (New York : Scholastic, Inc., 2013)
Princess Emily's sister, Lottie, is the newest member of the Rescue Princesses. She is excited to have animal adventures of her very own. When Lottie uncovers a plot to steal horses from the palace stables, she knows she must act. She is a Rescue Princess now -- if anyone can save those animals, it's her!
Keywords: Princesses -- Juvenile fiction; Animal rescue -- Juvenile fiction; Horses -- Juvenile fiction; Children's stories